Poverty and Educational Access from a Social Studies Education Perspective in Pontianak City - Rabiatul Alya; Ayuni Kartika; Mulia Sari; Lidya Ranti; Alya Fitriani; Fransiska Liska; Veronika Tiara Tiara; Glenn Hosea Fernando Ringkat; Korang Rose (CV. Yazri Aksara Nusantara, 2026)
Poverty Poverty is a structural social condition that significantly influences access to education. From a Social Studies Education perspective, poverty should be understood not merely as an economic constraint but as a social phenomenon closely linked to inequality, social justice, and civic development. This article examines the relationship between poverty and educational access in Pontianak City using the conceptual framework of Social Studies Education. Employing a qualitative literature-based design, the study analyzes secondary data drawn from official statistical reports, peer-reviewed journal articles, and relevant policy documents published over the past decade. The data were examined through thematic content analysis to identify social patterns shaping educational participation among economically disadvantaged groups. The findings indicate that poverty acts as a structural barrier through educational costs, household economic pressures, and unequal distribution of educational resources, resulting in differentiated educational trajectories. The study concludes that addressing educational inequality requires not only economic interventions but also socially responsive educational strategies that recognize poverty as a central issue in achieving inclusive and equitable education. Kemiskinan merupakan kondisi sosial struktural yang secara signifikan memengaruhi akses terhadap pendidikan. Dalam perspektif Pendidikan IPS, kemiskinan tidak hanya dipahami sebagai keterbatasan ekonomi, tetapi juga sebagai fenomena sosial yang berkaitan erat dengan ketimpangan, keadilan sosial, dan pembentukan kewargaan. Artikel ini mengkaji hubungan antara kemiskinan dan akses pendidikan di Kota Pontianak dengan menggunakan kerangka konseptual Pendidikan IPS. Penelitian ini menerapkan pendekatan kualitatif berbasis studi kepustakaan dengan menganalisis data sekunder yang bersumber dari laporan statistik resmi, artikel jurnal ilmiah, dan dokumen kebijakan dalam sepuluh tahun terakhir. Analisis isi tematik digunakan untuk mengidentifikasi pola sosial yang membentuk partisipasi pendidikan kelompok masyarakat kurang mampu. Hasil penelitian menunjukkan bahwa kemiskinan berperan sebagai hambatan struktural melalui biaya pendidikan, tekanan ekonomi rumah tangga, dan distribusi sumber daya pendidikan yang tidak merata. Penelitian ini menyimpulkan bahwa pengurangan ketimpangan pendidikan memerlukan intervensi ekonomi serta strategi pendidikan yang responsif secara sosial